Answer:
= -
![(1)/(8)](https://img.qammunity.org/2022/formulas/mathematics/college/rg98ozckf5lxwmpuro5ma5f58995vrv8np.png)
Explanation:
Given
=
( cross- multiply )
2(a - b) = 3(a + 2b) ← distribute parenthesis on both sides )
2a - 2b = 3a + 6b ( subtract 3a from both sides )
- a - 2b = 6b ( add 2b to both sides )
- a = 8b ( divide both sides by 8 )
-
a = b ( divide both sides by a )
-
=
![(b)/(a)](https://img.qammunity.org/2022/formulas/mathematics/college/ooprwno8vklvfvzej2vcsnnlk83a1n92rr.png)